2021
DOI: 10.3390/cancers13225809
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiac Glycoside Deslanoside Exerts Anticancer Activity in Prostate Cancer Cells by Modulating Multiple Signaling Pathways

Abstract: Prostate cancer (PCa) is a leading cause of cancer-related deaths among men worldwide, and novel therapies for advanced PCa are urgently needed. Cardiac glycosides represent an attractive group of candidates for anticancer repurposing, but the cardiac glycoside deslanoside has not been tested for potential anticancer activity so far. We found that deslanoside effectively inhibited colony formation in vitro and tumor growth in nude mice of PCa cell lines 22Rv1, PC-3, and DU 145. Such an anticancer activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…It has been reported that cardenolide glycosides have a dramatic anti-cancer role in diverse types of human cancers, such as PRAD [ 49 , 50 ]. The anti-cancer effect of cardenolide glycosides was associated with a variety of proteins and signaling pathways [ 51 , 52 , 53 ]. In the present study, malayoside was found to be critical to the suppression of the growth ( Figure 4 B) and induction of apoptosis ( Figure 4 C–H) in PRAD cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cardenolide glycosides have a dramatic anti-cancer role in diverse types of human cancers, such as PRAD [ 49 , 50 ]. The anti-cancer effect of cardenolide glycosides was associated with a variety of proteins and signaling pathways [ 51 , 52 , 53 ]. In the present study, malayoside was found to be critical to the suppression of the growth ( Figure 4 B) and induction of apoptosis ( Figure 4 C–H) in PRAD cells.…”
Section: Discussionmentioning
confidence: 99%
“…Extraction of RNA, construction of libraries using the SE100 protocol, and sequencing with a DNBSEQ platform with pair-end 100 bp sequencing length were performed by the Beijing Genomics Institute (Wuhan, China). Raw data processing was completed as previously described [14]. All RNA-seq data were processed by FASTQC for quality assessment and aligned to the human genome using Bowtie2 (V2.2.5) [27].…”
Section: Rna-sequencing and Bioinformatic Analysesmentioning
confidence: 99%
“…TGF-β plays a pivotal role in the development of bone metastasis, even though it suppresses cell proliferation and tumor growth in the early stages of tumorigenesis [8][9][10][11]. Although the TGF-β signaling is an attractive target for treating bone metastasis, directly targeting TGF-β and its receptors have proven challenging for different reasons [12][13][14]. For example, TGF-β has critical functions in tissue homeostasis [14], and TGF-β-targeting compounds are often not selective and thus could cause toxicities to cardiac tissues and skin [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Anticancer effects of cardiac glycoside deslanoside, which is found in the leaves of Digitalis lanata , were reported in PCa cell lines ( Figure 2 and Table 2 ) [ 55 ]. This drug shows in vitro antiproliferative activity and tumor growth inhibition in vivo on 22Rv1, PC3, and DU145 cells.…”
Section: Necroptosis and Necroptosis Inducers In Prostate Cancermentioning
confidence: 99%